Boosting the thermal conductivity of CNF-based composites by cross-linked lignin nanoparticle and BN-OH: Dual construction of 3D thermally conductive pathways. (1st March 2021) - Wang, Xiu; Qu, Yifei; Jiao, Liang; Bian, Huiyang; Wang, Ruibin; Wu, Weibing; Fang, Guigan; Dai, Hongqi
Abstract: The construction of thermally conductive pathways to improve the thermal conductivity of the thermal interface materials (TIMs) is highly demanded due to the expanding trend of miniaturization, integration, and high-power of microelectronics, whereas the present TIMs could hardly provide the satisfying heat management performance. Herein, we report a progressive 3D self-assembly strategy for the fabrication of a composite film with excellent flexibility and thermally conductivity. Hexagonal boron nitride (BN)-OH is cross-linked with lignin nanoparticle (LNP) by borax and assembled onto cellulose nanofibrils (CNF), after further freeze-drying and pressing the composite film is thus formed. SEM analysis revealed that the BN-LNP thermally conductive pathways were successfully formed, and LNP acted as the cross-linking point of BN-OH. The 50 wt% filler loaded BN-LNP/CNF composite (BN-LNP50) exhibited a through-plane thermal conductivity of 2.577 W/mK, while this feature for the pure CNF film was only 0.413 W/mK, revealing an improvement of ~524%. It is worth noting that at the same filler content, the composite loaded with non-cross-linked BN/LNP mixture presented a much lower thermal conductivity (1.224 W/mK) compared to that was loaded with BN-LNP (2.084 W/mK). Particularly, the BN-LNP50 was thermally decomposed at 230 °C, demonstrating an increasement of 30% compared with the pure CNF film. Overall, this study provides an effective approach to fabricate BN-related thermally conductive materials with improved thermal management capacity. Graphical abstract: Image 1